2020
DOI: 10.1080/03007995.2020.1775072
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and economic burden of hyperkalemia in the United States Medicare population

Abstract: Objective: To estimate the prevalence and economic burden of hyperkalemia in the United States (US) Medicare population. Methods: Patients were selected from a 5% random sample of Medicare beneficiaries (01 January 2010-31 December 2014) to estimate the prevalence and economic burden of hyperkalemia. The prevalence for each calendar year was calculated as the number of patients with hyperkalemia divided by the total number of eligible patients per year. To estimate the economic burden of hyperkalemia, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
2
32
1
Order By: Relevance
“…Hyperkalemia recurrence also increased with severity (mild: 13.3%, moderate: 15.4%, severe: 18.4% within 30 days). The post-discharge outcomes reported in this study are comparable to a retrospective cohort study that assessed the burden associated with hyperkalemia readmissions 30, 60, and 90 days post-discharge [21]. In that study, hyperkalemia-related hospitalizations were associated with significantly more readmissions than hospitalizations unrelated to hyperkalemia (30 days: 12.5% vs. 8.4%; 60 days: 18.3% vs. 12.7%; 90 days: 24.3% vs. 16.8%; all p < 0.001) [21].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Hyperkalemia recurrence also increased with severity (mild: 13.3%, moderate: 15.4%, severe: 18.4% within 30 days). The post-discharge outcomes reported in this study are comparable to a retrospective cohort study that assessed the burden associated with hyperkalemia readmissions 30, 60, and 90 days post-discharge [21]. In that study, hyperkalemia-related hospitalizations were associated with significantly more readmissions than hospitalizations unrelated to hyperkalemia (30 days: 12.5% vs. 8.4%; 60 days: 18.3% vs. 12.7%; 90 days: 24.3% vs. 16.8%; all p < 0.001) [21].…”
Section: Discussionsupporting
confidence: 58%
“…Despite the frequent occurrence of hyperkalemia in hospitalized patients, scant recent real-world evidence is available regarding patient outcomes following hospitalization [15,[18][19][20]. A recent study found that patients with hyperkalemia-related hospitalizations have significant post-discharge economic and readmission burdens [21,22]. However, evidence that comprehensively and longitudinally describes both the inpatient management and post-discharge outcomes by hyperkalemia severity is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Mu et al analysed a 5% random sample of Medicare beneficiaries in the US between 2010 and 2014 and randomised them based on the presence of hyperkalaemia (potassium level >5 mEq/l). [ 58 ] Those with hyperkalaemia had more inpatient admissions, outpatient and emergency department visits and skilled nursing care facility admissions. Patients with hyperkalaemia and concomitant HF and/or CKD had even higher rates of hospital visits and longer inpatient stays.…”
Section: Economic Impactmentioning
confidence: 99%
“…While there are several published observational studies comparing HRU and healthcare expenditures for patients with and without HK 2,[12][13][14][15] , research regarding the relative effect of different treatment modalities among patients with HK are emerging 14,[19][20][21][22][23][24][25] . Among Medicare Advantage patients with HK in real-world clinical practice, this study aimed to evaluate the outcomes for patients exposed to patiromer compared to patients not exposed to a K + binder.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the United States (US), the prevalence of HK was reported to be 1-2% overall, and potentially as high as 15% among Medicare patients with CKD and/or CHF 11,12 . HK has been reported to be associated with increased healthcare costs and healthcare resource utilization (HRU; eg, inpatient admission and emergency department [ED] encounters) [13][14][15] . In studies using administrative claims data in the US, researchers found that patients with HK incurred 58% higher total healthcare expenditures and were 40% more likely to be readmitted, compared to patients without HK 12,15 .…”
Section: Introductionmentioning
confidence: 99%